Comparison of paravertebral block vs. general anesthesia for percutaneous nephrolithotomy: A retrospective study - Fei, Miaomiao; Qin, Wendong; An, Guanghui; Li, Dujian; Li, Cheng; Xiong, Lize (Frontiers in Medicine, 2023)
Background: General anesthesia is used in the majority of patients undergoing percutaneous nephrolithotomy. To reduce the general anesthesia-related risks and complications, this study evaluated the efficacy and safety of the paravertebral block as a novel and alternative anesthetic method for percutaneous nephrolithotomy. Methods: This was a retrospective study. A total of 198 patients under percutaneous nephrolithotomy were included. Among them, 76 patients received paravertebral block and 122 received general anesthesia. Patients’ characteristics, surgical outcomes, anesthetic outcomes, and perioperative complications and the visual analogue scale (VAS) were recorded to evaluate the efficacy and safety of paravertebral block compared with general anesthesia. Intergroup differences of the parameters were analyzed using an independent t test and χ2-tests appropriate. Results: Seventy-six patients who underwent paravertebral block completed the surgery successfully, three patients were supplemented with propofol for discomfort during ureteroscopy, and two patients were supplemented with remifentanil for incomplete nerve blockade. Patients who underwent paravertebral block had a higher American Society of Anesthesiologists grade and heart function grade, including patients with contraindications to general anesthesia. Intraoperative and postoperative adverse events and the anesthesia costs were less in patients who underwent paravertebral block. VAS pain scores during the postoperative period in patients who underwent paravertebral block were lower than those in patients who underwent general anesthesia without the use of patient-controlled intravenous analgesia. Conclusions: In this retrospective study, paravertebral block was found to be effective and safe in providing intraoperative anesthesia for percutaneous nephrolithotomy, and had less adverse events and anesthesia costs. Paravertebral block is an attractive alternative anesthesia for patients at increased risk of comorbidities following general or neuraxial anesthesia.